Systemic characteristic of safety profile of monoclonal antibodies used in rheumatology practice - A. V. Philippova; A. S. Kolbin; E. V. Verbitskaya; S. V. Glagolev; V. A. Polivanov (Izdatelstvo OKI, 2019)
Monoclonal antibodies are highly effective medications, which made a breakthrough in medicine. Taking into consideration the properties of monoclonal antibodies safety plays a key role in "risk-benefit" assessment. For monoclonal antibodies this remains studied insufficiently. The article presents a systemic characteristic of safety profile of monoclonal antibodies used in rheumatology, based on the database of spontaneous reports of the Federal Service for the Supervision of Healthcare. Specified greater alertness of Russian practitioners regarding the risk of developing tuberculosis infections in comparison to their foreign counterparts. Spontaneous reports of the development of neoplasms and deviations of laboratory tests, according to our data, on the contrary, are reported less. It is advisable to draw the attention of practitioners to the peculiarities of work with isolated deviations in laboratory tests and keep alert about the safety issues of monoclonal antibodies in general. It is important to continue monitoring to characterize delayed type D adverse drug reactions.